The effect of ad blocking on website traffic and quality. (9th February 2018) - Shiller, Benjamin; Waldfogel, Joel; Ryan, Johnny
Abstract: Ad blocking software allows Internet users to obtain information without generating ad revenue for site owners, potentially undermining investments in content. We explore the impact of site‐level ad blocker usage on website quality, as inferred from traffic. We find that each additional percentage point of site visitors blocking ads reduces its traffic by 0.67% over 35 months. Impacted sites provide less content over time, providing corroboration for the mechanism. Effects on revenue are compounded; ad blocking reduces visits, and remaining visitors blocking ads do not generate revenue. We conclude that ad blocking poses a threat to the ad‐supported web.